Determinant Faktor Keberhasilan Toilet Training Pada Anak Toddler Di Rw 002 Perumahan Sinar Pamulang, Tangerang Selatan - Rita Dwi Pratiwi (STIKes Kharisma Persada, 2021)
Toilet training is an attempt to train children to be able to control bowel movement (BAB) or urinate (BAK). Toilet training can be done in the child's independence phase, which usually begins at the age of 18-36 months. The objective of this research was to recognize whether there is any correlation between the level of knowledge of mothers just given counseling, on her attitude in the implementation of the toilet training and keep participating actively in toilet training on all children aged 18 -36 months in 002 Hamlet, the Sinar Pamulang Housing Regency, South Tangerang. This study used a quantitative method. It used children to commit an analytic design with the cross-sectional approach, the number of the sample was 61 significant proportion of respondents, with a purposive sampling method, and used a questionnaire to prove data collection. The result of this research obtained there was a correlation knowledge of mothers with their attitude about toilet training (p value 0,000), knowledge of mothers for the implementation of the toilet training (p value 0,000), knowledge of mothers for the success of toilet training (p value 0,002), attitudes of the mother with the implementation of the toilet training (p value 0,017), attitudes of the mothers with the success of toilet training (p value 0,004), consistency of participating actively in the implementation of the toilet training (p value 0,000). The fit and proper test of logistic regression showed that the dependent variable for which the most influence to successful toilet training is the implementation of the mother toilet training (p value 0,011) with a value of up (persons of very = 5,73). The results of this study can be a consideration for educational institutions, especially for students in the effort to optimize the growth of children by disseminating information about mother's knowledge, mother's attitudes, implementation, and success of toilet training.